(untitled) (World Bulletin of Social Sciences, 2025)
This study examines the reasons for the emergence of distance education and its necessity, the organization of distance education in Uzbekistan, as well as the work being carried out by integrating international experience and achievements of the national methodology. It discusses the achievements in this field, the methods effectively used in distance learning, particularly in distance literary education, and their positive impact on teaching literature in higher education.